Implementing Integrity and Character Education Through Hypnoteaching in Elementary Schools: A Case Study Analysis - Dewi Ermawati; Triyanto; Idam Ragil Widianto Atmojo (Didaktika: Jurnal Kependidikan, 2025)
The decline in academic integrity, marked by increasing cases of cheating and ethical breaches, underscores the urgency for innovative character education approaches. This study evaluates the application of integrity character education using hypnoteaching methods at SDN Bendo 2 Sukodono. Employing a qualitative case study design, data were collected through participatory observation, self-assessment questionnaires, and in-depth interviews with key stakeholders, including principals, teachers, and students in grades IV to VI. Results show significant effectiveness, with implementation scores averaging 81.7% for teachers and 84.3% for students. The highest performance was noted in positive language use (92.5%), while honest behavior improved as 69.7% of students reported no integrity violations. However, challenges persist, including imitative behavior (51.2%) and low acceptance of collective decisions (15%). This study highlights hypnoteaching's potential to enhance character education and recommends systematic teacher training and continuous evaluation to sustain these positive outcomes.